2019
DOI: 10.3390/polym11020340
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and Desorption Studies of Pb(II) and Ni(II) from Aqueous Solutions by a New Composite Based on Alginate and Magadiite Materials

Abstract: A new composite material based on alginate and magadiite/Di-(2-ethylhexyl) phosphoric acid (CAM-D2EHPA) was successfully prepared by previous impregnation of layered magadiite with D2EHPA extractant, and then immobilized into the alginate matrix. Air dried beads of CAM-D2EHPA were characterized by FTIR and SEM–EDX techniques. The sorbent was used for the separation of lead and nickel from nitrate solutions; the main parameters of sorption such as contact time, pH of the solution, and initial metal concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 56 publications
1
24
1
Order By: Relevance
“…The theoretical values of adsorption reported in the literature for alginate beads vary. The values for Ni 2+ range from 25.60 mg/g obtained by Al-Rub, A. et al [36] to 97.93 mg/g obtained by Nastaj, J. et al [37]. The values of the current study were below the values for adsorption of Ni 2+ by alginate beads reported in the literature.…”
Section: Analysis Of Adsorption Isothermscontrasting
confidence: 68%
“…The theoretical values of adsorption reported in the literature for alginate beads vary. The values for Ni 2+ range from 25.60 mg/g obtained by Al-Rub, A. et al [36] to 97.93 mg/g obtained by Nastaj, J. et al [37]. The values of the current study were below the values for adsorption of Ni 2+ by alginate beads reported in the literature.…”
Section: Analysis Of Adsorption Isothermscontrasting
confidence: 68%
“…Polymeric materials have been extensively studied for their application in toxic metals removals, such as alginate-based composite [10], β-cyclodextrin nano-sponge [11], and cellulose membrane [12]. Other than those polymers, polyurethane (PU) has gained many interests in academic research for its adsorption ability to remove multiple heavy metal ions [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…They have concerned issues related to the development of technologies that use activated sludge in various forms [7][8][9][10][11]; the bioaugmentation of reactors [12,13], biofilm, and hybrid techniques [14,15]; and the preliminary preparation and pre-treatment of sewage sludge and back-side waters [16,17]. New research has also covered alternative technologies, e.g., sorption which may be used for the removal of a big amount of organic and inorganic pollutants and which can be used in conjunction with several techniques (such as flocculation-coagulation) [18][19][20].…”
Section: Introductionmentioning
confidence: 99%